Komunikasi Interpersonal Dalam Peningkatan Kinerja Pegawai di Dinas Komunikasi dan Informatika Provinsi Sumatera Utara (Studi Gender) - Sazali, Hasan; Putra Siregar, Harry Pratama (TIN: Terapan Informatika Nusantara, 2020)
This article discusses interpersonal communication in improving the performance of employees at the North Sumatra Province Information and Information Technology Office, previously named Kanwil Department of Information, North Sumatra Province, abbreviated as Kanwil Deppensu until December 27, 2001, and since December 27 2001 the name has changed to Sumatra Information and Communication Agency. North which is better known as Bainfokom. Since 2007 until now Bainfokom has changed its name to the Office of Communication and Information of North Sumatra Province, abbreviated as Diskominfo Provsu. This research uses qualitative research with a descriptive approach. Interpersonal communication in this office runs well and is able to maintain the performance of employees who work